HUBUNGAN IKLIM ORGANISASI SEKOLAH DAN SUPERVISI AKADEMIK DENGAN KINERJA MENGAJAR GURU SMA NEGERI DI KABUPATEN KUBU RAYA - Darsita, Darsita; Sindju, Herculanus Bahari; Martono, Martono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the contribution of school organizational climate and academic supervision of the teacher’s teaching perpormance high schools in Kubu Raya district either partially or simultaneously. this study is an ex post facto study uses a quantitative approach to associantive forms. Population of 201 high school teachers in the state of Kubu Raya district. While the study sample was 134 teachers randomly selected by simple random sampling technique. data obtained by questionnaire instrument and analyzet with descriptive statistics and inferential statistics using multiple regression. The results of data analysis showed: (1) School Organizational climate in SMA of Kubu Raya district includes most of the categories the data quite well with the contribution of school organizational climate are 52.99%. While supervision in conducted the pincipal academic high schools in Kubu Raya district includes most of the categories quite well with the contribution of academic supervision are 40.30%. For the performance of teachers to teach high schools in Kubu Raya district includes most of the categories with the contribution performance of teachers are 42.54%, (2) There is a significant relationship between organizational climate schools with teachers teaching performance high schools in the District Kubu Raya, (3) There is a significant relationship between academic supervision by teachers teaching performance high schools in Kubu Raya District, (4) There is a significant relationship betweet school organizational climate and academic supervision together with teacher teaching performance high schools in the Distric Kubu Raya.Keyword: School Organizational Climate, Academic Supervision, Teacher’s Performance